INTEGRATION-INTERCONNECTION OF KNOWLEDGE IN ISLAMIC EDUCATION AS A SOLUTION OF CONTEMPORARY EDUCATIONAL PROBLEMS - Husain, Andi Musthafa; Ulum, Miftahul (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2020)
The current concept and implementation of education in Islam so far has not shown excellence in solving community problems in an applicative-operational manner. This is because Muslims are often trapped in dichotomous thinking distinguishing Islamic knowledge from non-Islamic knowledge. Islamic education is only considered as related to “hereafter world” which only regulates theoretical relationships. The worldly problems are considered not too important, which ultimately makes Islamic education stresses more on religious sciences. This in turn creates a very wide gap because education in Islam is focused on revelation. As a result, Islamic education has not been able to get involved in the contemporary social and humanist realm. Against this backdrop, it seems that there is a pressing need to reexamine the concept of education in Islam to make it more empowering, critical, and creative. The book entitled “Rereading the Concept of Education in Islam” written by Dr. Hujair AH Sanaky, MSi is one of the attempts to re-examine the concept of education in Islam by dismantling the dichotomy between Islamic education and education and offering a design of education in Islam that is more integrative and responsive to the demands of changing societies and times.